CD36 is upregulated in mice with periodontitis and metabolic syndrome and involved in macrophage gene upregulation by palmitate. (13th January 2017) - Lu, Z; Li, Y; Brinson, CW; Kirkwood, KL; Lopes‐Virella, MF; Huang, Y
Abstract : Background: We reported that high‐fat diet (HFD)‐induced metabolic syndrome (MetS) exacerbates lipopolysaccharide (LPS)‐stimulated periodontitis and palmitate, the major saturated fatty acid in the HFD, amplified LPS‐stimulated gene expression in vitro . As CD36 is a major receptor for fatty acids, we investigated periodontal CD36 expression in mice with periodontitis and MetS, and the role of CD36 in inflammatory gene expression in macrophages stimulated by palmitate. Methods: MetS and periodontitis were induced in mice by HFD and periodontal injection of LPS, respectively. The periodontal CD36 expression and its relationship with alveolar bone loss were studied using immunohistochemistry, real‐time PCR, and correlation analysis. The role of CD36 in upregulation of inflammatory mediators by LPS and palmitate in macrophages was assessed using pharmacological inhibitor and small interfering RNA. Results: Periodontal CD36 expression was higher in mice with both MetS and periodontitis than that in mice with periodontitis or MetS alone and was correlated with osteoclastogenesis and alveolar bone loss. In vitro studies showed that CD36 expression in macrophages was upregulated by LPS and palmitate, and targeting CD36 attenuated palmitate‐enhanced gene expression. Conclusion: CD36 expression is upregulated in mice with periodontitis and MetS and involved in gene expression in macrophages stimulated by palmitate and LPS.